Siponimod exerts neuroprotective effects on the retina and higher visual pathway through neuronal S1PR1 in experimental glaucoma - Basavarajappa, Devaraj; Gupta, Vivek; Chitranshi, Nitin; Wall, Roshana; Rajput, Rashi; Pushpitha, Kanishka; Sharma, Samridhi; Mirzaei, Mehdi; Klistorner, Alexander; Graham, Stuart (Neural regeneration research, 2023)
Sphingosine-1-phosphate receptor (S1PR) signaling regulates diverse pathophysiological processes in the central nervous system. The role of S1PR signaling in neurodegenerative conditions is still largely unidentified. Siponimod is a specific modulator of S1P1 and S1P5 receptors, an immunosuppressant drug for managing secondary progressive multiple sclerosis. We investigated its neuroprotective properties in vivo on the retina and the brain in an optic nerve injury model induced by a chronic increase in intraocular pressure or acute N-methyl-D-aspartate excitotoxicity. Neuronal-specific deletion of sphingosine-1-phosphate receptor (S1PR1) was carried out by expressing AAV-PHP.eB-Cre recombinase under Syn1 promoter in S1PR1flox/flox mice to define the role of S1PR1 in neurons. Inner retinal electrophysiological responses, along with histological and immunofluorescence analysis of the retina and optic nerve tissues, indicated significant neuroprotective effects of siponimod when administered orally via diet in chronic and acute optic nerve injury models. Further, siponimod treatment showed significant protection against trans-neuronal degenerative changes in the higher visual center of the brain induced by optic nerve injury. Siponimod treatment also reduced microglial activation and reactive gliosis along the visual pathway. Our results showed that siponimod markedly upregulated neuroprotective Akt and Erk1/2 activation in the retina and the brain. Neuronal-specific deletion of S1PR1 enhanced retinal and dorsolateral geniculate nucleus degenerative changes in a chronic optic nerve injury condition and attenuated protective effects of siponimod. In summary, our data demonstrated that S1PR1 signaling plays a vital role in the retinal ganglion cell and dorsolateral geniculate nucleus neuronal survival in experimental glaucoma, and siponimod exerts direct neuroprotective effects through S1PR1 in neurons in the central nervous system independent of its peripheral immuno-modulatory effects. Our findings suggest that neuronal S1PR1 is a neuroprotective therapeutic target and its modulation by siponimod has positive implications in glaucoma conditions.